A theory of aggregate consumption - Yun K. Kim; Mark Setterfield; Yuan Mei (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2014)
We develop a Keynesian model of aggregate consumption. Our theory emphasizes the importance of the relative income hypothesis and debt finance for understanding household consumption behavior. It is shown that particular importance attaches to how net debtor households service their debts, and that the treatment of debt-servicing commitments as a substitute for savings by these households creates the potential for 'sudden stops' in consumption spending (and hence aggregate demand). An earlier version of this paper was presented at the University of Leeds in October 2012. The authors would like to thank two anonymous referees, Barry Cynamon, and seminar participants at the University of Leeds for their helpful comments. Any remaining errors are our own.
Keywords: E12; E21; 330; consumption; household borrowing; household debt; relative income hypothesis